Etyczne i ekonomiczne aspekty programu agrarnego Henryka Kamieńskiego - Szymański, Zdzisław (Annales. Etyka w Życiu Gospodarczym, 2008)
Henryk Kamieński (1813–1866), a philosopher, economist, and theorist of struggle for nationalindependence, idealized petty ownership as the most appropriate form of ownership both in ethical andeconomic aspects. He analyzed the problem on three levels. In his proposals for a specific solution ofthe agrarian question, presented in the Warsaw periodicals, Kamieński supported the introduction ofagricultural rent paid by peasants and the abolishment of serfdom. Calling serfdom a land usury hadan ethical implication. In the protection of the manor over peasants Kamieński sees the desire of manorowners to hold the victims of this usury in their hands. Replacement of serfdom with an agricultural rentwas for him the first step in granting landownership to peasants.Kamieński emphasizes that petty ownership is conducive to production growth. He believes thatthe spread of it is an opportunity for peasants to heighten their national consciousness and a chance ofcivilized advancement of Polish territories. This line of thinking is clearly evident in his studiespublished abroad, devoted to the conception of combining a national uprising with granting freehold topeasants.Kamieński also discusses the values of petty ownership in agriculture in his theoretical workFilozofia ekonomii materialnej ludzkiego społeczeństwa [Philosophy of material economics of humansociety], in which he presents his vision of a system of social justice. For him, petty ownership isa guarantee of respect for human rights, the most effective safeguard of preserving the autonomy ofhuman individual. In this reasoning we could see certain elements of personalism, which bringsKamieński’s standpoint closer to that of Pope John Paul II.